¡Democracia en el país y en la casa! Mouvement des femmes et conceptualisation de la violence de genre dans le Chili de Pinochet - Anne-Claire Sanz-Gavillon (Nuevo mundo - Mundos Nuevos, 2014)
In this article, our purpose is to reconstitute and analyze the processes that have made possible, in the Chilean society, the beginning of a reflection about the political dimension of the private sphere, which can be seen as the first step of the conception of a public policy designed to eradicate the so-called violencia intrafamiliar. By studying, in the very particular context of the dictatorship, the origin of the women’s movement and the feminist movement and the work they both did to conceptualize the gender-based violence between sentimental partners as a social problem, we will try to define the transformations of the interpretative structures used to think the relationships between genders that this new approach supposed. Our work is based on interviews of ex-members of the Chilean feminist movement and on the story of a women’s organization – Casa Yela – which perfectly illustrates our demonstration.